The Influence of Principal Transformational Leadership on Teacher Performance and Learning Quality in Schools - Utami, Batina Yulia; Nelitawati, Nelitawati; Al-Kadri, Hanif (Postgraduate School, Universitas Negeri Padang, 2024)
This study found that principals who adopt transformational leadership can improve morale, staff satisfaction, and student engagement in the educational process. This leadership also plays a role in building a positive, inclusive, and collaborative school culture, which supports the achievement of educational goals effectively. This study confirms that attention to individual well-being, appropriate support, and open and responsive communication between principals and teachers are essential to improving teacher performance and job satisfaction. The results show that a positive principal leadership style can improve teacher productivity and job satisfaction, which in turn has an impact on improving the quality of learning and student learning outcomes. However, the implementation of transformational leadership faces challenges such as lack of understanding of the concept and uncertainty about the changes needed. Therefore, a clear understanding and adequate resources are needed to support teacher professional development and the implementation of consistent and effective leadership strategies. In conclusion, transformational leadership by principals is essential to creating a harmonious and empowering educational environment, which can bring positive changes in the world of education.